Evaluation of fertilization strategies for the establishment and productivity of Xaraés grass - N. M. Lage Filho; A. R. Lopes; D. F. Araújo; V. H. M. Macedo; C. Faturi; T. C. Silva; A. C. Rêgo; W. L. Silva; F. N. Domingues (Boletim de Indústria Animal)
Soil correction and fertilization are important in the formation of pastures, but many producers neglect them or use ineffective alternatives. Slow-release fertilizers may harm the establishment of forage plants, as this is a crucial moment during the pasture formation stage. The objective was to evaluate establishment fertilization strategies on the morphogenic, structural characteristics and productivity of Xaraés grass (Urochloa brizantha cv. Xaraés). To this end, two experimental trials were conducted in a greenhouse, both under a completely randomized design. In the first, three establishment fertilization strategies were tested (strategy 1: without lime/NPK; strategy 2: lime + NPK; strategy 3: natural reactive phosphate), with six replications. In the second, a 3 × 10 factorial scheme was used, corresponding to the three establishment fertilization strategies and 10 evaluation dates (32, 39, 46, 53, 60, 67, 74, 81, 88, and 95 days) after emergence. of plants (DAE). In experiment 1 the morphogenic characteristics of the plant were evaluated, in the second the structure and dry mass production of the aerial part and roots of Xaraés grass were evaluated Higher (P<0.05) rates of leaf elongation and appearance, stem elongation, and leaf senescence, in addition to higher (P<0.05) tiller densities and dry mass production, were obtained in strategy 2 than in the others. Forage production of Xaraés grass increased linearly (P<0.05) as a function of higher DAE. Therefore, using lime together with NPK fertilization provides greater growth and production of Xaraés grass.